The relationship between polyarticular hypermobility and the incidence of injuries in children aged 6-10 years - Dwulit, Alicja; Weber-Nowakowska, Katarzyna (Journal of Education, Health and Sport, 2018)
Introduction. The polyarticular hipermobility is a disorder in the connective tissue. It is a frequent disorder observed in school-aged children, with a more frequent occurrence in the female sex. Because of the increased elasticity of the soft tissues, children with hypermobility are more likely to suffer from injuries. The aim of the study is to assess the relationship between polyarticular hypermobility and the incidence of injuries in the group of children aged 6-10 years. Materiał and methods. The study group consisted of 102 children aged 6-10. All oft them are students from primary schools in Szczecin. The study was conducted using a available 9-point Beighton scale. Polyarticular hypermobility according to Beighton test is diagnosed after getting at least 4 points of maximum 9. The evaluation of 4 or more points was received by 35 children, and they constituted the test group (n1). The control group (n2) consisted of 35 randomly selected children with no identified polyarticular hypermobility. 21 children from examined groups (n1, n2) had a history of injury. Results. There were no statistically significant correlation for the incidence of injuries in children with hypermobility and children without hypermobility (p = 0,603). There is no statistically significant correlation between the class profile and the occurrence of an injury in the study group (p = 0,245 Conclusions 1. Injuries are a common occurrence among children in early school age. 2. The incidence of injuries in the group of children 6-10 years is not dependent on polyarticular hypermobility. 3. Polyarticular hypermobility predisposes to sports (swimming, gymnastics, acrobatics).